PENGARUH PROFITABILITAS, LIKUIDITAS, DAN SOLVABILITAS TERHADAP NILAI PERUSAHAAN - Elizabeth Yustina Andy, Jonnardi (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This study aimed to examine the influence of firm profitability, firm liquidity, and firm solvability toward firm value. The population in this research is a number of 54 companies listed on the Indonesia Stock Exchange 2014-2018. The number of samples is 48 companies over the past five years, there are 240 samples. Sample was selected by using simple random sampling method. Data processing techniques in this research using program Eviews version 10.0. The results of this research indicate that all independent variables simultaneously have a significant effect on firm value. The partially test indicate that profitability has positive and significant effect on firm value, liquidity has negative and significant effect on firm value, while solvability has not significant effect on firm value.